Investigation into the Phase–Activity Relationship of MnO2 Nanomaterials toward Ozone‐Assisted Catalytic Oxidation of Toluene. Issue 50 (31st October 2021) - Yang, Ruijie; Guo, Zhongjie; Cai, Lixin; Zhu, Rongshu; Fan, Yingying; Zhang, Yuefeng; Han, Pingping; Zhang, Wanjian; Zhu, Xiangang; Zhao, Qitong; Zhu, Zhenye; Chan, Chak Keung; et al.
Abstract: Manganese dioxide (MnO2 ), with naturally abundant crystal phases, is one of the most active candidates for toluene degradation. However, it remains ambiguous and controversial of the phase–activity relationship and the origin of the catalytic activity of these multiphase MnO2 . In this study, six types of MnO2 with crystal phases corresponding to α‐, β‐, γ‐, ε‐, λ‐, and δ‐MnO2 are prepared, and their catalytic activity toward ozone‐assisted catalytic oxidation of toluene at room temperature are studied, which follow the order of δ‐MnO2 > α‐MnO2 > ε‐MnO2 > γ‐MnO2 > λ‐MnO2 > β‐MnO2 . Further investigation of the specific oxygen species with the toluene oxidation activity indicates that high catalytic activity of MnO2 is originated from the rich oxygen vacancy and the strong mobility of oxygen species. This work illustrates the important role of crystal phase in determining the oxygen vacancies' density and the mobility of oxygen species, thus influencing the catalytic activity of MnO2 catalysts, which sheds light on strategies of rational design and synthesis of multiphase MnO2 catalysts for volatile organic pollutants' (VOCs) degradation. Abstract : Six types of MnO2 (α‐, β‐, γ‐, ε‐, λ‐, and δ‐MnO2 ) are prepared, and these crystals follow the activity order of δ‐MnO2 > α‐MnO2 > ε‐MnO2 > γ‐MnO2 > λ‐MnO2 > β‐MnO2 toward O3 ‐assisted catalytic oxidation of toluene. Importantly, the high activity of multiphase MnO2 may originate from the rich oxygen vacancy and the strong mobility of oxygen species.